Biosensors in Cancer Research: A New Frontier in Screening, Diagnosis and Treatment Management - Gupta, Seema (Journal of Neonatal Surgery, 2025)
Cancer is a type of genetic-related disease that some cells become unnormal and form cancer clusters or tumours and it is one of the main causes of death for humans. While qualified treatment and adequate survivorship care in the early stages of cancer can improve survival rates and reduce side effects, most of the early cancer symptoms or signs are not obvious and specific enough to be observed and recognize. Therefore, reliable, cost-effective, and powerful technologies to detect the disease are needed. Cancer biomarkers are substances such as nucleic acids, enzymes, and metabolites, present in cancer clusters, tumours, or serum. While biosensors provide a quick, accurate, sensitive, uncomplicated, and economical method of diagnosing a particular cancer biomarker and is important to cancer detection and treatment, especially early diagnosis. Biosensors could be classified into three types: mass-based, electrochemical, or optical biosensors. With the development of science and technology and continuous research, more biosensors are designed for advanced technology, such as nanotechnology. The new and novel biosensors provide a powerful way for cancer detection. The objective of this research is to discuss the novel biosensors designed in recent years for screening, diagnosis and treatment management of cancers